Combining concurrent radiotherapy and immunotherapy for synergistic effects in recurrent endometrial cancer - A case report - Luiza Chepkemoi; Oluwaseyi Ajayi; Nancy Anabaraonye; Onyinye D. Balogun (Elsevier, 2022)
Endometrial cancer, also known as uterine cancer, is the second most common cancer affecting women globally and the fourth most prevalent in the United States (US). Treatment often involves a combination of surgery, radiotherapy and chemotherapy depending on the severity. In this case report, we present two patients with relapsed endometrial carcinomas, who responded positively to combined radiotherapy and immunotherapy followed by maintenance immunotherapy.Given the worsening prognoses associated with recurrent endometrial cancers, these two cases warrant the further exploration of the concurrent administration of immunotherapy and radiation therapy in the context of clinical trials.